A homotopy approach to rational covariance extension with degree constraint - Enqvist, Per (Zielona Góra: Uniwersytet Zielonogórski)
The solutions to the Rational Covariance Extension Problem (RCEP) are parameterized by the spectral zeros. The rational filter with a specified numerator solving the RCEP can be determined from a known convex optimization problem. However, this optimization problem may become ill-conditioned for some parameter values. A modification of the optimization problem to avoid the ill-conditioning is proposed and the modified problem is solved efficiently by a continuation method.
Keywords: stochastic realization theory; rational covariance extension problem; ARMA model design; continuation method; optimization